Family Educational Style and its Relationship to Aggressive Behavior among High School Students )It is a Field Research in Ranya( - Dastan Omer Mahmood; Juan Ismail Bakr (Zanco Journal of Humanity Sciences)
Family educational practices are one of the issues whose effects and consequences are not immediately apparent. That is, the parental educational style may not have an immediate effect on the child, but it may have effects and consequences during adolescence or youth. Consequently, family educational patterns directly and indirectly determine individual behavior patterns, including aggressive behaviors. The main objective of the study is to find the relationship between family parenting styles with aggressive behavior patterns. The researcher also used the descriptive analytical method to analyze the objectives. For this purpose, he prepared a form that consisted of 38 items for family education and 26 items for aggressive behavior. Meanwhile, a random sample of 400 high school students in Ranya, including) 212( males and )188( females, was selected. The researcher used both SPSS and AMOS statistical programs.